Transport of DNA repair proteins to the cell nucleus by the classical nuclear importin pathway – a structural overview - Fontes, Marcos R.M. [UNESP] (2025)
DNA repair is a crucial biological process necessary to address damage caused by both endogenous and exogenous agents, with at least five major pathways recognized as central to this process. In several cancer types and other diseases, including neurodegenerative disorders, DNA repair mechanisms are often disrupted or dysregulated. Despite the diversity of these proteins and their roles, they all share the common requirement of being imported into the cell nucleus to perform their functions. Therefore, understanding the nuclear import of these proteins is essential for comprehending their roles in cellular processes. The first and best-characterized nuclear targeting signal is the classical nuclear localization sequence (NLS), recognized by importin-α (Impα). Several structural and affinity studies have been conducted on complexes formed between Impα and NLSs from DNA repair proteins, although these represent only a fraction of all known DNA repair proteins. These studies have significantly advanced our understanding of the nuclear import process of DNA repair proteins, often revealing unexpected results that challenge existing literature and computational predictions. Despite advances in computational, biochemical, and cellular assays, structural methods – particularly crystallography and in-solution biophysical approaches – continue to play a critical role in providing insights into molecular events operating in biological pathways. In this review, we aim to summarize experimental structural and affinity studies involving Impα and NLSs from DNA repair proteins, with the goal of furthering our understanding of the function of these essential proteins.